Access to Guns in the Heat of the Moment: More Restrictive Gun Laws Mitigate the Effect of Temperature on Violence - Jonathan Colmer; Jennifer L. Doleac (Center for Economic Studies and ifo Institute (CESifo), 2023)
Gun violence is a major problem in the United States, and extensive prior work has shown that higher temperatures increase violent behavior. In this paper, we consider whether restricting the concealed carry of firearms mitigates or exacerbates the effect of temperature on violence. We use two identification strategies that exploit daily variation in temperature and variation in gun control policies between and within states. Our findings suggest that more prohibitive concealed carry laws attenuate the temperature-homicide relationship. Additional results suggest that restrictions primarily decrease the lethality of temperature-driven violent crimes, rather than their overall occurrence, but may be less effective at reducing access to guns in more urban areas.
Keywords: K42; Q51; I18; 330; right-to-carry; temperature; crime; homicide